THE IMPACT OF RESILIENCE AND COMPASSION FATIGUE ON JOB SATISFACTION AND TURNOVER INTENTION AMONG CRITICAL CARE NURSES IN SAUDI ARABIA - Sajdh Mashl Alshammari, Maha Atieh Alshammari, ‏Ibtisam Aswad Alanazi, Ahmed Alhumaidi Ahmed Alatmi, Sattam Hamid Muhammad Alshammari, Hussah Muazi Aldhafeeri, Badriya Saber Alenazi, Munif Matar Khabur Aldhafeeri, (Chelonian Research Foundation, 2022)
Nursing is a demanding profession that requires a high level of dedication, empathy, and emotional resilience. Critical care nurses, in particular, face unique challenges due to the high-stress environment, critical patient conditions, and the need for rapid decision-making (Alharbi et al., 2019). These factors can lead to increased risk of compassion fatigue, a state of emotional and physical exhaustion resulting from prolonged exposure to traumatic or stressful events (Cocker & Joss, 2016). Compassion fatigue can negatively impact nurses' well-being, job satisfaction, and intention to remain in their current position or the nursing profession altogether (Zhang et al., 2018). Resilience, the ability to adapt and bounce back from adversity, has been identified as a key factor in helping nurses cope with work-related stress and maintain their psychological well-being (Guo et al., 2018). Nurses with higher levels of resilience may be better equipped to handle the challenges of critical care nursing, leading to increased job satisfaction and reduced turnover intention (Kutluturkan et al., 2016). This study aims to investigate the impact of resilience and compassion fatigue on job satisfaction and turnover intention among critical care nurses in Saudi Arabia.